School media resource libraries in Singapore : an assessment and potential developments. - Tan, Chay Ngee. (2008)
This study was to examine the current status and potential development of school media resource libraries (SMRLs) in Singapore in the context of the emerging information society. A questionnaire was used for collecting data and 31 schools participated in this study.